2018
DOI: 10.21037/apc.2018.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging radiotherapy strategies for pancreatic adenocarcinoma: stereotactic, intensity modulated and particle radiotherapy

Abstract: The role of radiotherapy for locally advanced pancreatic cancer (LAPC) is unclear based on studies that used conventional doses and fractionation schedules. Modern radiotherapy techniques have not been studied in depth, however. We reviewed the literature on emerging methods of delivering higher doses of conformal radiotherapy using stereotactic body radiation, intensity modulated radiation, and particle beam radiation, highlighting clinical outcomes and toxicities. The literature review suggests low rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…As many as 40% of pancreatic cancer patients are diagnosed with locoregionally advanced disease or progress during the course of the disease [154]. The infiltration of nerves in the area surrounding the pancreas is observed in 43–72% of patients, which causes severe pain [155]. Delivering median 28 Gy (25–33 Gy) in 5 fractions using SBRT resulted in abdominal pain relief in 78% of advanced pancreatic cancer patients [156].…”
Section: Radiation Therapy For Painful Primary/regional/metastaticmentioning
confidence: 99%
“…As many as 40% of pancreatic cancer patients are diagnosed with locoregionally advanced disease or progress during the course of the disease [154]. The infiltration of nerves in the area surrounding the pancreas is observed in 43–72% of patients, which causes severe pain [155]. Delivering median 28 Gy (25–33 Gy) in 5 fractions using SBRT resulted in abdominal pain relief in 78% of advanced pancreatic cancer patients [156].…”
Section: Radiation Therapy For Painful Primary/regional/metastaticmentioning
confidence: 99%
“…Numerous authors have confirmed the feasibility and safety of SBRT in pancreatic cancer with standard linacs, achieving 1-year local control of 80% in locally advanced pancreatic cancer (LAPC), even if the first experiences were burdened by high rates of ≥3 grade gastrointestinal toxicity, representing a significant dose limiting factor [2530].…”
Section: Introductionmentioning
confidence: 99%
“…respiratory gating) and Image Guided Radiotherapy (IGRT) techniques (i.e. CBCT, CT-on-rails) contributed in reducing gastrointestinal side effects and escalating the dose to the target volumes, reaching higher biological equivalent doses [25, 31].…”
Section: Introductionmentioning
confidence: 99%
“…The recent focus of neoadjuvant treatment strategies for LAPC lies in investigating more effective chemotherapy schemes, such as FOLFIRINOX (leucovorin, 5-fluorouracil, irinotecan, and oxaliplatin) [ 13 , 14 , 15 , 16 , 17 ], and subsequent CRT or RT with modern techniques (e.g., stereotactic, intensity modulated, and particle RT) [ 18 ]. The high failure rate of RT in PDAC can be attributed to the high intrinsic radioresistance of the tumors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%